2020
DOI: 10.7759/cureus.8129
|View full text |Cite
|
Sign up to set email alerts
|

Phenolisation of the Sinus Tract in Recurrent Sacrococcygeal Pilonidal Sinus Disease: A Prospective Cohort Study

Abstract: Phenolisation is a minimally invasive treatment option in patients with primary pilonidal disease. However, most studies focus on patients with primary pilonidal sinus disease, while data of patients with recurrent pilonidal disease are very scarce. The purpose of this study was to evaluate phenolisation of the sinus tract in patients with recurrent pilonidal sinus disease after previous surgery for SPSD. Methods This single-center prospective cohort study included 60 patients with recurrent pilonidal disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…First, the overall response rate was low at 27%. This is common for survey-based research involving health professionals [10][11][12]. This may result in a response bias in our study, where only individuals who felt strongly about the utility of the DRE or the level of DRE training they received would have responded to the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…First, the overall response rate was low at 27%. This is common for survey-based research involving health professionals [10][11][12]. This may result in a response bias in our study, where only individuals who felt strongly about the utility of the DRE or the level of DRE training they received would have responded to the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…No economic costs were incurred due to the difficulty of quantifying the cost of sick leave. However, in the bibliography, it is described that patients treated with phenolization and the median loss of days of normal daily activities was 5.0 (1.0–12.0) days and 89.5% of patients resumed normal daily activities after 2 weeks 31 …”
Section: Discussionmentioning
confidence: 99%
“…However, in the bibliography, it is described that patients treated with phenolization and the median loss of days of normal daily activities was 5.0 (1.0-12.0) days and 89.5% of patients resumed normal daily activities after 2 weeks. 31 The statistical studies developed by Calvo et al, showed that the average sick leave of patients with SPD was 50 days. The predictive factors of longer sick leave were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Infections after perineal surgeries such as pilonidal cyst excisions or surgeries for rectal prolapse may also manifest as coccygeal pain. When these procedures have occurred near the time of onset of symptoms, infection should be of high suspicion for the cause of pain, and an appropriate workup should be initiated 3,4,11,16,18,19 . When coccydynia is not associated with the hallmark coccygeal tenderness on physical examination, this may be an indication of radicular or referred pain 13 .…”
Section: Etiologymentioning
confidence: 99%